The using of theatre as a teaching tool in the technical course in agriculture: a case study (Research, Society and Development, 2021)
Brazilian elementary and technical teaching is lacking of application of alternative educational tools for obtaining an excellent level of education, which provides human and citizen development. Among the various playful alternatives, the application of theatrical technique stands out, which offers an opportunity for disinhibition and development of virtues such as creativity, resilience, patience, cooperation and proactivity. This work aimed to evaluate the use of theatre in the discipline of Animal Science I, a signature offered to students in the first year of the technical course in Agriculture at the Federal Institute of Education, Science and Technology of Minas Gerais - Bambuí campus, and its influence on the training process. The methodology was applied to the classes of 2017, 2018 and 2019 and evaluated through the application of an electronic questionnaire to the participating students, obtaining 34 respondents. Considering that the maximum score of the activity was 2.0 points, the average score was 1.80 (90% of the total value), which reveals the students' commitment to the proposal. However, a considerable portion (40%) did not attend the presentation. In general, the students positively evaluated the theatre, especially with regard to aspects related to shyness and agreed that this tool was important to develop creativity, proactivity and cooperation. Thus, the theatre methodology can be a significant item in the process of training subjects and provide the development of “soft skills”, a growing demand in today's 4.0 society.